Lethal hemorrhagic necrotizing pancreatitis in a child with congenital immunodeficiency and COVID-19 - Zahradníková, Petra; Jáger, René; Pechanová, Rebeka; Fedorová, Lenka; Béder, Igor; Barloková, Dominika; Nedomová, Barbora; Švajdler, Peter; Babala, Jozef (Journal of pediatric surgery case reports, 2022)
Purpose: Various manifestations of coronavirus (SARS-CoV-2) have been reported since the pandemic began. Some articles have reported acute pancreatitis in adult patients due to COVID-19 infection. To our knowledge this is the first report of acute hemorrhagic necrotizing pancreatitis in children associated with SARS-CoV-2 infection. Case presentation: A 7-year-old girl with congenital immunodeficiency was referred to the intensive care (ICU) unit with acute respiratory distress syndrome. She required mechanical ventilation (MV) due to pulmonary involvement of COVID-19 (chest CT with lower lung ground-glass opacities). SARS-CoV-2 infection was laboratory confirmed. Following a 49-day stay in the ICU, due to the clinical and radiological signs of acute abdomen and to the rapid deterioration in the clinical status, an indication to proceed an urgent surgerical intervention was made. Intra-operatively an adhesiolysis with blunt dissection of the of gastrocolic ligament was performed, then followed by debridement of the necrotic pancreas (more than 1⁄2 of the pancreas was damaged). Continuous lavage and drainage were placed. During the post-operative period, patient required aggressive MV and insulin therapy for persistent hyperglycemia. The CT scans reported a necrosis of the pancreas and we observed amylase and lipase elevation in the peritoneal lavage sample. Despite active intensive therapy, the patient's condition did not improve and she died 38 days after laparotomy as a result of multi-organ failure. Conclusion: The mechanism for the development of acute haemorrhagic necrotizing pancreatitis in the COVID-19 positive patients is unclear; perhaps it is due to a direct cytopathic effect from the COVID-19 virus, or due to the ACE2 expression in pancreas.